Language Outcomes in Deaf or Hard of Hearing Teenagers Who Are Spoken Language Users: Effects of Universal Newborn Hearing Screening and Early Confirmation. Issue 5 (September 2017) - Pimperton, Hannah; Kreppner, Jana; Mahon, Merle; Stevenson, Jim; Terlektsi, Emmanouela; Worsfold, Sarah; Yuen, Ho Ming; Kennedy, Colin R.
Abstract : Objectives: This study aimed to examine whether (a) exposure to universal newborn hearing screening (UNHS) and b) early confirmation of hearing loss were associated with benefits to expressive and receptive language outcomes in the teenage years for a cohort of spoken language users. It also aimed to determine whether either of these two variables was associated with benefits to relative language gain from middle childhood to adolescence within this cohort. Design: The participants were drawn from a prospective cohort study of a population sample of children with bilateral permanent childhood hearing loss, who varied in their exposure to UNHS and who had previously had their language skills assessed at 6–10 years. Sixty deaf or hard of hearing teenagers who were spoken language users and a comparison group of 38 teenagers with normal hearing completed standardized measures of their receptive and expressive language ability at 13–19 years. Results: Teenagers exposed to UNHS did not show significantly better expressive (adjusted mean difference, 0.40; 95% confidence interval [CI], −0.26 to 1.05; d = 0.32) or receptive (adjusted mean difference, 0.68; 95% CI, −0.56 to 1.93; d = 0.28) language skills than those who were not. Those who had their hearing loss confirmed by 9 months of age did not show significantly better expressive (adjusted mean difference, 0.43; 95% CI, −0.20 to 1.05; d = 0.35) or receptive (adjusted mean difference, 0.95; 95% CI, −0.22 to 2.11; d = 0.42) language skills than those who had it confirmed later. In all cases, effect sizes were of small size and in favor of those exposed to UNHS or confirmed by 9 months. Subgroup analysis indicated larger beneficial effects of early confirmation for those deaf or hard of hearing teenagers without cochlear implants (N = 48; 80% of the sample), and these benefits were significant in the case of receptive language outcomes (adjusted mean difference, 1.55; 95% CI, 0.38 to 2.71; d = 0.78). Exposure to UNHS did not account for significant unique variance in any of the three language scores at 13–19 years beyond that accounted for by existing language scores at 6–10 years. Early confirmation accounted for significant unique variance in the expressive language information score at 13–19 years after adjusting for the corresponding score at 6–10 years (R 2 change = 0.08, p = 0.03). Conclusions: This study found that while adolescent language scores were higher for deaf or hard of hearing teenagers exposed to UNHS and those who had their hearing loss confirmed by 9 months, these group differences were not significant within the whole sample. There was some evidence of a beneficial effect of early confirmation of hearing loss on relative expressive language gain from childhood to adolescence. Further examination of the effect of these variables on adolescent language outcomes in other cohorts would be valuable.